Pro-Resolving Mediator Annexin A1 Regulates Intracellular Ca2+ and Mucin Secretion in Cultured Goblet Cells Suggesting a New Use in Inflammatory Conjunctival Diseases - Lyngstadaas, Anne V.; Olsen, Markus V.; Bair, Jeffrey A.; Hodges, Robin R.; Utheim, Tor P.; Serhan, Charles N.; Dartt, Darlene A. (Frontiers in Immunology, 2021)
The amount of mucin secreted by conjunctival goblet cells is regulated to ensure the optimal level for protection of the ocular surface. Under physiological conditions lipid specialized pro-resolving mediators (SPM) are essential for maintaining tissue homeostasis including the conjunctiva. The protein Annexin A1 (AnxA1) can act as an SPM. We used cultured rat conjunctival goblet cells to determine if AnxA1 stimulates an increase in intracellular [Ca2+] ([Ca2+]i) and mucin secretion and to identify the signaling pathways. The increase in Ca2+i was determined using fura2/AM and mucin secretion was measured using an enzyme-linked lectin assay. AnxA1 stimulated an increase in [Ca2+]i and mucin secretion that was blocked by the cell-permeant Ca2+ chelator BAPTA/AM and the ALX/FPR2 receptor inhibitor BOC2. AnxA1 increased [Ca2+]i to a similar extent as the SPMs lipoxin A4 and RvD1 and histamine. The AnxA1 increase in [Ca2+]i and mucin secretion were inhibited by blocking the phospholipase C (PLC) pathway including PLC, the IP3 receptor, the Ca2+/ATPase that causes the intracellular Ca2+ stores to empty, and blockade of Ca2+ influx. Inhibition of protein kinase C (PKC) also decreased the AnxA1-stimulated increase in [Ca2+]i and mucin secretion. In contrast inhibitors of Ca2+/calmodulin-dependent protein kinase II, ERK 1/2, phospholipase A2 (PLA2), and phospholipase D (PLD) did not alter AnxA1-stimulated increase in [Ca2+]i, but did inhibit mucin secretion. Activation of protein kinase A did not decrease either the AnxA1-stimulated rise in [Ca2+]i or secretion. We conclude that in health, AnxA1 contributes to the mucin layer of the tear film and ocular surface homeostasis by activating the PLC signaling pathway to increase Ca2+i and stimulate mucin secretion and ERK1/2, PLA2, and PLD to stimulate mucin secretion from conjunctival goblet cells.